Quelques traits généraux de la diversité sylvatique des Petites Antilles - Philippe Joseph (VertigO)
The geomorphologics differences of Lesser Indies lead variations of climatic factors which influence the processes of selection of the species. On the mountainous islands, the pluviometric altitudinal gradients bound bioclimatic floors packaging the development of potential forest types. Of uneven spatial distribution on the scale of the archipelago, these differ as long from the structural and architectural point of view that biocenotique. Generally speaking, every plant floor is characterized by a floral potential (the stock or the collection of species) from which the diverse biotopes condition (package) the floral ascendancies (phytocenoses). Between these island microsystems, the mesologic differences led a high biological variety which the anthropisation stressed from the beginning of the Amerindian setelmen (occupation), approximately 4 000 years ago. Towards the diverse political statutes and in the perspective of the sustainable development, the preservation of the biodiversity, essential for the territorial management future, can be efficient only in the archipelagic scale.